AN OVERVIEW OF THE INDIAN PHARMACEUTICAL INDUSTRY (CAHIERS MAGELLANES-NS, 2024)
The Indian pharmaceutical industry has emerged as a global leader, driven by its remarkable growth and capabilities over the past few decades. Known for its cost-effective and quality-driven approach, this sector plays a crucial role in improving healthcare accessibility worldwide. With a remarkable global market share of over 20% in terms of global export volume, India is the largest provider of generic drugs globally, with pharmaceutical exports standing at around $24.6 billion in 2021-22. The country's strength lies in its generic drug manufacturing capabilities, but it is also making strides in the research and development of novel drug molecules. One of the key factors driving the growth of the Indian pharma industry is its ability to manufacture high-quality drugs at significantly lower costs compared to their Western counterparts. Despite the cost advantage, Indian pharmaceutical companies adhere to stringent global quality standards, including those set by the World Health Organization (WHO), U.S. Food and Drug Administration (FDA), and other regulatory bodies. The Indian government has played a pivotal role in supporting the growth of the pharmaceutical industry through various initiatives and policies, including tax incentives, patent reforms, and the establishment of dedicated pharma parks and clusters. The government's "Pharma Vision 2020" aimed to make India a global leader in end-to-end drug manufacturing and a hub for pharmaceutical innovation. Despite its impressive growth, the Indian pharmaceutical industry faces several challenges, including increasing competition from other low-cost manufacturing hubs, regulatory hurdles, and the need for more robust intellectual property protection. Looking ahead, the industry is well-positioned to capitalize on the growing global demand for affordable and quality healthcare solutions, with continued investments in R&D, adherence to international quality standards, and supportive government policies.